STEAM教育理論融入運動器材科技課程設計之教學效能評量 - 梁嘉文; 沙麗娃; 陳羿揚; 邱文信; Chia-Wen, Liang; Sha Liwa; Yi-Yang Chen; Wen-Hsin Chiu (國立交通大學體育室, 2020)
目的：運用STEAM教育理論開發運動器材科技課程教材，及探討如何整合跨領域師資及知識，提升大專體育系學生學習運動器材科技教學效能。方法：以16名學生參與STEAM教育理論融入運動器材科技課程，每週實施1次課程，每次2小時，為期18週。教學效能評量採用College Student Experience Questionnaire （CSEQ）為主要參考評量，透過校級校務研究中心以因素分析構面效度後提供本研究使用，分為教師教學方法、課堂內容、課堂內容與教材滿意度、課堂教學成效與滿意程度以及學生學習經驗等五大面向，控制組為某大學參與教學實踐其他8門STEAM教教育理論的，共117人。結果：以STEAM教育理論融入運動器材科技課程檢驗教學效能，從問卷結果顯示在教師教學方法、課堂內容、課堂內容與教材滿意度、課堂教學成效與滿意程度以及學生學習經驗等，五種教學效能面向均優於其他教學實踐課程。結論：建議教師在未來擬定運動器材科技設計相關課程時，可以參酌STEAM教育理論融合至教學模式，能提升教學效能。

Purpose: The purpose of this research was to used STEAM education theory to develop teaching materials for sports equipment technology courses, and to explore how to integrate cross-field teachers and knowledge to improve the teaching effectiveness of sports equipment technology for college sports students. Method: 16 students participated in the course of STEAM education theory integrated into sports equipment technology, and the course was implemented once a week, 2 hours each time, for 18 weeks. The teaching effectiveness evaluation adopts the College Student Experience Questionnaire (CSEQ) as the main reference evaluation, and provides the use of this research after the school-level school affairs research center analyzes with factor for aspects and validity. It was divided into five aspects: teachers' teaching methods, class content, satisfaction about class content and teaching materials, class teaching effectiveness and satisfaction, and students' learning experience. The control group was the students of a university participating in the other 8 courses in pedagogical practice. Results: Testing the teaching effectiveness of integrating STEAM education theory into sports equipment technology curriculum. The results of the questionnaire showed that the five teaching effectiveness dimensions about teachers' teaching methods, class content, satisfaction about class content and teaching materials, class teaching effectiveness and satisfaction, and students' learning experience were superior to other pedagogical practice courses. Conclusion: Teachers were suggested to consider the mode that integrating STEAM education theory into teaching when drafting related courses on sports equipment technology design in the future, which can improve teaching effectiveness.
The Teaching Effectiveness Evaluation of STEAM Education Theory Integrated Into the Design of Sports Equipment Technology Curriculum
Keywords: STEAM教育; 多媒體教材; 運動器材科技; 作品設計; 學習動機; STEAM education; multimedia teaching materials; sports equipment technology; work design; learning motivation